Valuation of Ecosystem Services Provided by Biodiversity Conservation: An Integrated Hydrological and Economic Model to Value the Enhanced Nitrogen Retention in Renaturated Streams - Ingo Bräuer; Rainer Marggraf (Fondazione Eni Enrico Mattei (FEEM), 2004)
The importance of ecosystem functions for humankind is well known. But only few attempts have been undertaken to estimate the economic value of these ecosystem services. In particular, indirect methods are rarely used, even though they are most suitable for the task. This discrepancy is because quantitative knowledge of changes in ecosystem functions is scarce. This paper presents a user-friendly procedure to quantify the increased N-retention in a renaturated river using easily available data. In a case study of the renaturated River Jossa (Germany) the benefits of increased nitrogen retention caused by beaver reintroduction are determined by using the replacement cost method. The quantification of chemical processes is discussed in detail, as well as the problems of defining an adequate reference scenario for the substitute costs. Results show that economic benefits from the evaluated ecosystem service ( exteuro12,000/annum) equal 12% of the total costs of the corresponding conservation scheme.
Keywords: D61; D62; Q2; Q25; 330; Biodiversity conservation programmes; Cost-benefit-analysis; Replacement cost method; Ecosystem services; Nutrient retention; Artenvielfalt; Umwelt; Bewertung; Gewässerschutz; Altlastensanierung; Kosten-Nutzen-Analyse; Deutschland